sin ( x + y ) = lo g ( x + y )
Find the value of d x d y .
Note that we didn't give you the base of the logarithm, you should not specifically assume that the logarithm is in base e or 10.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shouldn't the question be ln ( x + y )
I thought the derivative of lo g ( x ) is x ln ( 1 0 ) 1
That is a valid point, but it doesn't affect this solution. The solution set of cos t = t k is going to be a discrete set for any value of k . This means that x + y in the neighborhood of a point must be a constant.
Because it's a calculus question, I almost always assume that they mean ln , unless there is evidence to the contrary.
why not just solve for dy/dx algebraically in that first equation. you get dy/dx = -(cos(x+y)+ 1/(x+y)) / (cos(x+y)+1/(x+y) = -1
no need to do anything fancy with t as a parameter.
Yes, that is what I did too, if you look at the first line. However, the concern here, is that you need to deal with the case where cos ( x + t ) − x + y 1 = 0 (slight error in your working), since otherwise 0 0 = 1 .
You simply assumed that was not possible, which may not be the case. The thing is that, even in those cases, we will still have d x d y = − 1 .
Log is increasing from − ∞ to ∞ . Sin oscillates between -1 and 1. Therefore, there will be some value of x + y = c such that sin c = lo g c . Then, it's clear that d x d y = d x d ( c − x ) = − 1 .
Problem Loading...
Note Loading...
Set Loading...
Differentiate implicitly with respect to y, we have
( cos ( x + y ) − x + y 1 ) ( 1 + d x d y ) = 0 .
To solve cos ( x + y ) − x + y 1 = 0 , let x + y = t . Then, we have cos t = t 1 . We claim that the solution set consists of isolated points, which you can show by differentiating. Thus x + y = t is a constant and so d x d y = − 1 .
To solve the second factor, we get d x d y = − 1 immediately.